Adherence to proper blood pressure measurements among interns at the university of Gondar specialized referral hospital - Getnet, Mihret; Getahun, Amare Belete; Bitew, Desalegn Anmut; Getu, Ayechew Adera (Frontiers in Cardiovascular Medicine, 2025)
IntroductionBlood pressure is a lateral force exerted on the wall of arteries and is critical for the normal distribution of blood containing nutrients and oxygen to metabolic tissues. It is one of the vital signs often measured by interns, nurses, and physicians at doctor’s offices, at bedside, and possibly at home. Accurate blood pressure measurement is essential for proper diagnosis and management of patients, especially those with hypertension. The aim of this cross-sectional survey study is to assess the practice of measuring blood pressure by interns.MethodsThis study was conducted in the form of a survey administered through face-to-face interviews. All the interns at the Univeristy of Gondar Specialized Referral Hospital were approached. The survey included questions about devices used, patient's information, and blood pressure measurement techniques. Epi-Data version 3.1 was used for data entry and exported to STATA 17 for data management and analysis. The Chi-square test was checked to assess the eligibility of variables for logistic regression. Finally, in the multivariable binary logistic regression analysis, variables with P-value < 0.05 were considered to be statistically significantly associated. The Adjusted Odds Ratio (AOR) with 95% CI was reported to declare the statistical significance and strength of association between blood pressure measurement and independent variables.ResultThe magnitude of appropriate measurement of blood pressure among interns was 10.1 (95% CI: 7.19, 13.9). A total of 318 interns participated in the current study. Of these study participants, 65.4% (208) were males. A increase in participants age (AOR: 1.48, 95% CI: 1.09, 2.01), being male interns (AOR: 5.51, 95% CI: 1.51, 8.97), and having patients who were familiar with the procedure (AOR: 2.95, 95% CI: 1.19, 7.03) were factors significantly associated with appropriate adherence to blood pressure measurement.Conclusion and recommendationOnly 10% of six-year medical students (Interns) were successful in appropriately assessing blood pressure. Age, being male, and patient understanding were factors significantly associated to the adherence of blood pressure measurement. Considering the frequency of BP measurement and the impact of hypertension on morbidity and mortality, efforts are needed to maximize the quality of BP measurement by health professionals. This process should begin early during training and be consistent throughout their clinical practice, supplemented by ongoing education.